2022
DOI: 10.3767/persoonia.2022.49.02
|View full text |Cite
|
Sign up to set email alerts
|

About spirals and pores: Xylariaceae with remarkable germ loci

Abstract: Based on phylogenetic analyses of a multi-gene matrix of nuITS-LSU rDNA, RPB2 and TUB2 sequences and morphology, xylariaceous species with uni- to pauciperitheciate stromata and ascospores having a spirally coiling (helicoid) germ slit are revised and reclassified, including detailed descriptions and illustrations. The genus Helicogermslita is redefined and restricted to seven species with massive, erumpent, clypeus-like carbonaceous stromata, and Rosellinia somala is combined in Helicogermslita. Within the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 83 publications
2
9
0
Order By: Relevance
“…The MP analysis revealed two trees of length 20,490 (not shown) that had a similar topology to the ML tree. The phylogenies reveal a monophyletic clade of Nemania (including Euepixylon ), like in previous studies ( Wendt et al 2018 ; Pi et al 2021 ; Samarakoon et al 2022 ; Voglmayr et al 2022 ). Within Xylariaceae , the Nemania clade is most closely related to the genera Coniolariella , Dematophora , Entoleuca and Rosellinia .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The MP analysis revealed two trees of length 20,490 (not shown) that had a similar topology to the ML tree. The phylogenies reveal a monophyletic clade of Nemania (including Euepixylon ), like in previous studies ( Wendt et al 2018 ; Pi et al 2021 ; Samarakoon et al 2022 ; Voglmayr et al 2022 ). Within Xylariaceae , the Nemania clade is most closely related to the genera Coniolariella , Dematophora , Entoleuca and Rosellinia .…”
Section: Resultssupporting
confidence: 84%
“…When re-establishing the genus Euepixylon , already Læssøe and Spooner (1993) doubted whether the genus will survive in the long run. Considering the results of the phylogenetic analyses, germ site morphology is clearly not a good character to separate Euepixylon from Nemania and the former genus should be considered as a synonym of the latter, which has already been implemented by for example, Pi et al (2021) and Voglmayr et al (2022) and which we, therefore, also adopt here. Synonymy of both genera is further supported by the fact that the type species of Euepixylon ( E. udum ), as well as Nemania ( N. serpens ), are revealed to be closely related within the Nemania subclade 1 (N1).…”
Section: Discussionmentioning
confidence: 99%
“…The most conspicuous feature of Spirodecospora is the spirally linear ornamentations surrounding the ascospores. Recent phylogenetic analysis on xylariaceous taxa revealed the existence of several genera having brown, unicellular ascospores with spirally coiling germ slits ( Voglmayr et al 2022 ). The spiral structure found in Spirodecospora was also originally regarded as a germ slit ( Vasilyeva 1990 ), but this interpretation was not accepted in later studies ( Lu et al 1998 , Mel’nik & Hyde 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although several spirodecospora-like genera ( e.g. Albicollum , Helicogermslita , Leptomassaria , and Spiririma ), which have helicoid germ slits around the ascospore, were shown phylogenetically to be found throughout Xylariaceae ( Voglmayr et al 2022 ), no sequence data are available for any species of Spirodecospora .…”
Section: Introductionmentioning
confidence: 99%
“…The asci lack an apical apparatus, and spores are not actively discharged but released after rupture Section Editor: Marco Thines Instituto de Bioprospeccíon y Fisiología Vegetal-INBIOFIV (CONICET-UNT), San Lorenzo 1469, 4000 San Miguel de Tucumán, Tucumán, Argentina of the ascomatal apex (Rodrigues and Samuels 1989). These characteristics are highly atypical of the Xylariales, but it has meanwhile been established that the characteristics of the teleomorph are not necessarily in agreement with the phylogeny of this order (Jaklitsch et al 2016;Wendt et al 2018;Voglmayr et al 2022). These modern, polyphasic taxonomic studies showed that in the Xylariales and other groups of Sordariomycetes, the teleomorphic characters have subordinate importance.…”
Section: Introductionmentioning
confidence: 99%